Microfluidic Chip-based Nucleic Acid Testing using Gingival Crevicular Fluid as a New Technique for Detecting HIV-1 Infection - Alex Willyandre; Ahmad Syaifuddin; Khoirul Anam; Agustin Wulan Suci (Journal of Dentistry Indonesia, 2013)
Transmission of HIV-1 infection by individuals in window period who are tested negative in conventional HIV-1 detection would pose the community with serious problems. Several diagnostic tools require specific labora-tory equipment, perfect timing of diagnosis, antibody to HIV-1, and invasive technique to get sample for examination, until high amount of time to process the sample as well as accessibility of remote areas. Many attempts have been made to solve those problems to come to a new detection technique. This review aims to give information about the current development technique for detection of HIV infection. Microfluidic Chip-based Nucleic Acid Testing is currently introduced for detection of HIV-1 infection. This review also cover the possible usage of gingival crevicular fluid as sample specimen that could be taken noninvasively from the individual. DOI: 10.14693/jdi.v18i2.63